222k views
3 votes
Solve the following system of equations.
2x + y = 3
x = 2y - 1

2 Answers

1 vote
2(2y-1)+y=3
y=1
x=2 x1 - 1
x=1
User Mahir Islam
by
6.0k points
5 votes
Using the substitution method.

2x + y = 3
x = 2y -1 Since x has been isolated already plug it into Equation 1

2(2y - 1) + y = 3 Solve for y.
4y - 2 + y = 3
+2 +2 Combine like terms and isolate y.
4y + y = 5
5y = 5 Isolate y by dividing both sides by 5
5y/5 = 5/5
y = 1

With y solved, solve either system for x.

x = 2(1) - 1
x = 2-1
x = 1

Solution is (1,1)


User Walid Saad
by
6.2k points